Impact of Cigarette Smoke on Clearance and Inflammation after Pseudomonas aeruginosa Infection - Drannik, Anna G; Pouladi, Mahmoud A; Robbins, Clinton S; Goncharova, Susanna I; Kianpour, Sussan; Stampfli, Martin R (American journal of respiratory and critical care medicine, 2004)
The object of this study was to investigate the impact of cigarette smoke on bacterial clearance and immune inflammatory parameters after infection with Pseudomonas aeruginosa in mice. We observed a delayed rate of bacterial clearance in smoke-exposed compared with sham-exposed mice. This was associated with increased inflammation characterized by greater numbers of neutrophils and mononuclear cells in the bronchoalveolar lavage. After infection, we observed increased levels of proinflammatory cytokines (tumor necrosis factor-alpha, interleukin-1beta, and interleukin-6) and chemokines (monocyte chemoattractant protein-1 [MCP-1] and macrophage inflammatory protein-2 [MIP-2]) as well as myeloperoxidase and proteolytic activity in the lungs of smoke-exposed compared with sham-exposed animals. Delayed clearance was associated with increased morbidity and greater weight loss of smoke-exposed mice. After delivery of inactivated bacteria, we observed a similar inflammatory response, clinical score, and tumor necrosis factor-alpha expression in smoke- and sham-exposed animals, suggesting that increased inflammation and altered clinical presentation are due to the delayed rate of bacterial clearance. Our findings suggest that cigarette smoke affects respiratory immune-inflammatory responses elicited by bacteria. We postulate that altered respiratory host defense may be implicated in smoking-related diseases such as chronic obstructive pulmonary disease.